(untitled) (Research, Society and Development, 2020)
The following article aims to analyze the implementation and execution of the 5S Program in a construction material company. The methodology of the study is qualitative, being a case study in the company, private organization, retailer, specialized in sales of construction materials, composed by a team of 15 employees. As a result, the study reveals that employees were flexible in accepting the change in organizational climate / culture through the application of this new tool, the study also revealed some limitations on the part of employees related to self-discipline, considering that employees were used to how things happened before the application of this 5s program. Finally, the results of the study show that the impact of the 5S tool on the company’s quality management was necessary to improve the organizational environment, as the 5s program brought great benefits in matters related to the organization, facilitating the visibility of documents, products in the day by day, as well as allowing the reduction of waste, also allowing the environment to be always clean, hygienic and pleasant not only for customers, but also for employees, not forgetting also that for this tool to be successful it is necessary that all collaborate for the common good, bringing this responsibility for self-discipline to employees.